2021
DOI: 10.1007/s11239-021-02466-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of potential pharmacokinetic drug interactions in patients with atrial fibrillation and changing from warfarin to non-vitamin K oral anticoagulant therapy

Abstract: Highlights• Proposed benefits of NOACs over warfarin include less drug interactions but increasing evidence suggest pharmacokinetic interactions can impact efficacy and safety of NOACs• Switching patients from warfarin to a NOAC in those with an indication of atrial fibrillation reduced the potential for pharmacokinetic drug interactions but there remained around 40% of patients concurrently taking at least one interacting drug whilst on NOACs• Pharmacokinetic drug interactions with NOACs may be under-recognis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…147 Patient preference and convenience of DOACs were also identified as a major reason for the switch from VKA to DOAC. 44 73 78 145 General practitioner or specialist recommendations were the top reasons for VKA to DOAC switch in the study by Bernaitis et al 148 In a survey of physicians managing ischaemic stroke in patients with AF, 83% said they routinely switched patients to a DOAC for those who experience ischaemic stroke on VKA while only 38% did so for patients experiencing ischaemic stroke while on DOAC. 149 The major reason for not switching while on DOAC was the paucity of randomised trial on switching.…”
Section: Reasons For Oac Switchingmentioning
confidence: 99%
“…147 Patient preference and convenience of DOACs were also identified as a major reason for the switch from VKA to DOAC. 44 73 78 145 General practitioner or specialist recommendations were the top reasons for VKA to DOAC switch in the study by Bernaitis et al 148 In a survey of physicians managing ischaemic stroke in patients with AF, 83% said they routinely switched patients to a DOAC for those who experience ischaemic stroke on VKA while only 38% did so for patients experiencing ischaemic stroke while on DOAC. 149 The major reason for not switching while on DOAC was the paucity of randomised trial on switching.…”
Section: Reasons For Oac Switchingmentioning
confidence: 99%
“…Cerebral amyloid angiopathy (CAA), which is one of the three pathological hallmarks of AD, is present in more than 80% of AD patients, is characterized by the accumulation of Aβ in cortical and leptomeningeal blood vessels, and can directly contribute to cognitive decline and dementia by causing vascular lesions [5][6][7][8]. Oral anticoagulant, such as warfarin and rivaroxaban, showed beneficial effects for the prevention and treatment of stroke associated with AF [9,10]. However, some reports indicated that the application of anticoagulant may increase the risk of intracerebral hemorrhages in patients with both CAA and atrial fibrillation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulant, such as warfarin and rivaroxaban, showed beneficial effects for the prevention and treatment of stroke associated with AF [9,10]. However, some reports indicated that the application of anticoagulant may increase the risk of intracerebral hemorrhages in patients with both CAA and atrial fibrillation [9][10][11][12]. Moreover, warfarin had a higher risk of cognitive impairment than the direct oral anticoagulant (DOAC) [13,14].…”
Section: Introductionmentioning
confidence: 99%